Constitution of Nepal and Political Development: Adaption and Challenges of Implication - Dahal, Girdhari (Janapriya Journal of Interdisciplinary Studies, 2018)
The present constitution- promulgated by the Constitutional Assembly (CA) in September, 2015 is the seventh written document in the constitutional history of Nepal which has institutionalized Federal Democratic Republic achieved after the success of peoples' movement of 2006. It was made based on the principles of constitutionalism. The constitution of Nepal has addressed different issues for a modern state and is regarded as a progressive, people oriented constitution. It has also paved paths for further economic development. It has opened door for rights of the people, political stability, restructuring of the state, and sustainable peace and development of the state. However, there are many prospects as well as numerous challenges for its proper implementation. Some Madhes based parties (People of Terai) and ethnic minorities have criticized the constitution for being unable to address their pertinent issues fully. However, they have involved in the process of constitution implementation by participating in first local, provincial and federal level election held under new constitution. So the government needs to bring the Madhesh based parties and other groups into a peaceful consensus and should pave a path for implementation of this constitution. At the same time, implementation of federalism, election of local bodies, sustainable peace, political stability and development are among other challenges faced by this constitution. Janapriya Journal of Interdisciplinary Studies, Vol. 6 (December 2017), Page: 148-159